Gender stereotypes in students sport interests - Prot, Franjo (Array, 2011)
Gender based stereotypes are influencing sport interests. Objective estimation of that influence enables positive practical actions. Recently it was demonstrated that the second principal component absorbs most of the information ascribed to gender stereotypes extracted from 52 sport preference measures of sport interests (Prot, Bosnar, Pišot and Pišot 2011). Regarding ongoing improvement of gender equity issues, FISU and IOC are synergistically and complementarily developing effective policies, practices and strategies to reach gender equality in every possible way. What is a nature of this effect on sport preferences in university students population is the main aim of this study. A sample of 905 university students was measured (347 males and 558 females with an average age of 20 years, 99.1% of them aged in range from 18 to 26 years). The participants were given a list of 52 sports to be evaluated on a five-point scale. The 52 colon vectors of original data matrix were standardized and transformed to 52 standardized principal components ordered according to the values of corresponding eigenvalues. Discriminative analysis was preformed regarding gender in the space of 52 principal components. Coefficient of canonical correlation in overall space is r52=0.740 (r52= 0.548). When information on gender is projected on the second principle component alone r2=0.639 (r22 =0.408) what preserves 74.45% of information of overall system of variables. The correlation between the second principal component and the overall space discriminative function is 0.863, the highest value in the vector of structure of discriminative function, and 0.639 when gender is projected on second principal components. Means on discriminative functions are positive for females and negative for males. The bipolar structure of such a synthetic measure of gender stereotypes component of sport interests enables us to classify sports interests form high positive values, moderate values and low values as feminine. On the opposite side, sport interests can be classified form high, moderate and low negative values as masculine. Finally, correlations for the third group of sports are oscillating around zero what enable to declare it as gender stereotype neutral sport interests.